Study Comparing Between Surgical Evacuation and Medical Management with Vaginal Misoprostol for Early Pregnancy Loss (Bangladesh Critical Care Journal, 2023)
Background: Early pregnancy loss is one of the most common clinical problems that is encountered in dailygynaecological practice. The aim of this study is to assess the effectiveness and acceptability of using vaginalmisoprostol for management of first trimester spontaneous incomplete abortion as an alternative to direct vaginalsurgical evacuation in our setting.Methods: This prospective randomized study was carried out in the Department of Obstetrics and Gynaecology inShaheed Ziaur Rahman Medical College Hospital, Bogra. from January 2008 to December 2008. This study performedon 400 patients with first trimester incomplete abortion between 8 and 12 weeks requesting medical management. Theywere divided into two groups according to patients’ choice; group (I) received 800 microgram misprostol vaginally bydigital insertion into the posterior fornix while group (II) underwent surgical vaginal evacuation directly under generalanesthesia.Results: Although vaginal surgical evacuation was successful in solving the problem in 100% of cases, misoprostol wassuccessful in 70% after 1st dose and remained incomplete 30% after administration of 2nd dose. The overall satisfactionwas slightly higher in the surgical group. No serious side effects or complications were reported in the misoprostolgroup. The incidence of excessive post-abortive bleeding was more in the misoprostol group than in the surgicalevacuation group (p = 0.049).Conclusion: Although vaginal surgical evacuation is more effective than misoprostol in solving the problem stillmedical treatment is effective and acceptable especially when surgical management is not available or risky or patientsrefuse to do surgical management.Bangladesh Crit Care J March 2023; 11 (1): 19-23